Analisis Kadar Asam Salisilat Pada Krim Anti Jerawat yang Diperjualbelikan Di Kota Makassar - Rahma wati; Andi Yunita Irwan P.; Nurhidayat Nurhidayat; Andi Haldin Haerunisya (Lontara Journal of Health Science and Technology, 2022)
Anti-acne creams are in great demand, especially for humans who have acne problems. In anti-acne creams, one of the compounds that is often added to achieve the desired effect is salicylic acid, which acts as a keratolytic, anti-inflammatory, analgesic, bacteriostatic, and fungistatic agent. According to the Regulation of the Head of the Food and Drug Supervisory Agency of the Republic of Indonesia No. HK.00.05.42.1018 of 2010 concerning cosmetics, salicylic acid is allowed if it does not exceed 2%. Salicylic acid works by increasing skin moisture and promoting the removal of dead skin cells. In acne treatment, salicylic acid works by reducing inflammation (swelling and redness) and clearing clogged pores. The purpose of this study was to analyze the levels of salicylic acid in anti-acne creams that are not registered with BPOM which are traded in Makassar City using qualitative and quantitative methods. The results of qualitative research with the color test method obtained 2 positive samples from 5 samples. In the quantitative test using the spectrophotometric method, the salicylic acid content in sample A was 1.2083% and sample B was 61.875%.